Modified Calcium Manganites for Thermochemical Energy Storage Applications - Miller, James E.; Babiniec, Sean M.; Coker, Eric N.; Loutzenhiser, Peter G.; Stechel, Ellen B.; Ambrosini, Andrea (Frontiers in Energy Research, 2022)
CaAl0.2Mn0.8O3-δ (CAM28) and CaTi0.2Mn0.8O3-δ (CTM28) are perovskite metal oxides developed for high-temperature thermochemical energy storage (TCES) applications, e.g., in support of air Brayton power generation. Previous reports for these compounds focus on the equilibrium non-stoichiometry (δ) as a function of temperature and oxygen partial pressure (pO2) and the endotherm (or exotherm) accompanying changes in δ resulting from thermal reduction (or re-oxidation). Herein, we report results for elemental substitution and doping (Al, Co, Fe, La, Sr, Ti, Y, Zn, and Zr) of calcium manganites (CM) that establish the preference for CAM28 and CTM28. Techniques employed include conventional (screening and equilibrium) and ballistically heated multi-cycle thermogravimetric analysis (TGA), conventional and high temperature (in-situ) X-ray diffraction (XRD), and differential scanning calorimetry (DSC). Forward-looking results for A-site Y-doped materials, e.g., Ca0.9Y0.1MnO3-δ (CYM910), establish a route to increasing the reduction enthalpy relative to CAM28 and CTM28, albeit at the expense of increased reduction temperatures and raw materials costs. A thermodynamic model presented for CAM28, but extendable to related materials, provides values for the reaction enthalpy and extent of reduction as a function of temperature and oxygen partial pressure for use in design efforts. Taken as a whole, the results support the choice of Al-doped CaMnO3-δ as a low-cost material for TCES in a high temperature air Brayton application, but point the way to achieving higher stored energy densities that could lead to overall cost savings.